2009
DOI: 10.1177/089686080902900511
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Magnesium Flux in Automated Peritoneal Dialysis

Abstract: Background Calcium and magnesium balance in continuous ambulatory peritoneal dialysis (CAPD) has been extensively studied with several of the different formulations of fluid available. Calcium and magnesium balance in automated PD (APD) is less well studied and the effect on Ca and Mg flux is unknown. Data on glucose polymer solutions are also lacking. This prospective observational study was undertaken to examine mass transfer of Ca and Mg in APD patients. Methods 12 patients on APD were studied for two 24-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Patients using these solutions are slightly hypermagnesaemic [ 37 , 39 , 40 ] (see Table 1 ). This is because the transfer of magnesium is, if diffusive, mostly into the patient and thus positive [ 39 , 41 ].…”
Section: Magnesium In Dialysis Patientsmentioning
confidence: 99%
“…Patients using these solutions are slightly hypermagnesaemic [ 37 , 39 , 40 ] (see Table 1 ). This is because the transfer of magnesium is, if diffusive, mostly into the patient and thus positive [ 39 , 41 ].…”
Section: Magnesium In Dialysis Patientsmentioning
confidence: 99%
“…This can be attributed to the difference in dialysate Mg concentrations as well as dietary restrictions between PD and HD patients. Still, the laboratory results do not reveal the exact state of Mg in the body, and serum Mg levels can be normal even as cellular Mg is depleted 22 . Therefore, Mg deficiency in the dialysis population might be more widespread than is commonly realized.…”
Section: Discussionmentioning
confidence: 98%
“…Notably, the Mg concentration in clinical peritoneal dialysate is relatively low (0.25–0.75 mEq/L) for the purpose of Mg elimination 42 , 47 , 48 . One cohort study showed mean serum Mg levels of 0.84 mEq/L in PD patients, and > 32% of this cohort had low serum Mg levels (defined as < 0.74 mEq/L).…”
Section: Discussionmentioning
confidence: 99%